Biomechanical Evaluation of Different Fixation Methods for Mandibular Anterior Segmental Osteotomy Using Finite Element Analysis, Part One: Superior Repositioning Surgery. Issue 1 (January 2016) - Kilinç, Yeliz; Erkmen, Erkan; Kurt, Ahmet
Abstract : Abstract: The aim of the current study was to comparatively evaluate the mechanical behavior of 3 different fixation methods following various amounts of superior repositioning of mandibular anterior segment. In this study, 3 different rigid fixation configurations comprising double right L, double left L, or double I miniplates with monocortical screws were compared under vertical, horizontal, and oblique load conditions by means of finite element analysis. A three-dimensional finite element model of a fully dentate mandible was generated. A 3 and 5 mm superior repositioning of mandibular anterior segmental osteotomy were simulated. Three different finite element models corresponding to different fixation configurations were created for each superior repositioning. The von Mises stress values on fixation appliances and principal maximum stresses ( P max ) on bony structures were predicted by finite element analysis. The results have demonstrated that double right L configuration provides better stability with less stress fields in comparison with other fixation configurations used in this study.